The Role of Social Media Networks in Enriching the Arabic Digital Content in Humanities and Sciences from the Perspective of Jordanian Universities’ Students - Badrakhan, Sawsan; Taha, Jamal; Haimur, Talal (Dirasat: Human and Social Sciences, 2022)
The study aims to identify the role of social media networks in enriching and supporting the Arabic digital content from the perspective of students at the faculties of humanities and sciences in the Jordanian universities and the possible obstacles. A questionnaire of (25) items was designed and administered electronically via WhatsApp, Instagram and Facebook to (488) students at the University of Jordan and Al-Ahliyya Amman University. The study reveals that the role of social media networks in enriching and supporting the Arabic Digital Content is significant while the obstacles of such enrichment and support is at a medium level. The present study does not show any statistically significant differences between the means that could be attributed to variables such as gender, university, faculty or academic year.